People Knowledge on HIV/AIDS - Soetji Andari (Jurnal Penelitian Kesejahteraan Sosial, 2015)
The highest number of people living with HIV/AIDS are of childbearing age. The cumulative proportion of people living with HIV/AIDS in Yogyakarta is located at the level of 20-29 years of age. High activity in this age group makes a lot of productive risky sexual behavior. In the number of persons over the last ten years has increased tenfold. The research is meant to find out about people’s knowledge on the spread of HIV/AIDS in Yogyakarta. This study used is descriptive method, a research procedure that produces descriptive data in the form of words written or spoken by persons or behavior that being observed. This research is directed at the background of the individual in holistic and detail describtion on the phenomena of various things about the knowledge of the various groups on HIV/AIDS. The results of the study shows that there are many who do not know the transmission mode of this virus. They do not know how the disease is transmitted and only know the transmission of disease when in contact with people living with HIV/AIDS. Nearly 50 percent of respondents of the communities living around people with HIV/AIDS can not name a single cause of HIV/AIDS. This means that public knowledge about the disease around the respondents are not widely known. However, the level of knowledge possessed by peers (peer group) is quite good, because they are able to explain the cause of the spread of HIV/AIDS. Similarly withPLWHA (People Living with HIV/AIDS) and OHIDA (People living with people with HIV/AIDS) are used as the respondents have a fairly good knowledge about the causes of the spread of HIV/AIDS.